KESENGJANGAN PENDAPATAN PROVINSI DI KAWASAN TIMUR INDONESIA PERIODE 2005 - 2010 - Vera Paulin Kay (Jurnal Administrasi Terapan, 2022)
Indonesia have different area characteristic belonging area of nature resources,human resources,social condition and culture,with conduct area because the area characteristic have strong effect of formed development economic,so that’s not astonishing,when the pattern of economic development in Indonesia area,is not control and wiil be effect to the ability to grow and wiil be caused to several area can grow quickly but the other area grow slowly.But the way,the ability for growing is different and wiil be caused disparity of development conduct area.Disparity of development will go on and formed the aspect and dimension.Based on the condition the purpose of this research to analized the disparity of development which become conduct the province in east Indonesia area.The kinds of data which used in this research is data secunder. Data which need is data Gross National Product of province,based on constsnt price.Based on the achivment research,showed that value index disparity of conduct province in east Indonesia area is differentin high level. Key Words: Disparity, Gross National Product